2015
DOI: 10.1007/s12035-015-9125-2
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Flavonoid Pinocembrin: Molecular Targets and Potential Therapeutic Applications

Abstract: Pinocembrin is a natural flavonoid compound extracted from honey, propolis, ginger roots, wild marjoram, and other plants. In preclinical studies, it has shown anti-inflammatory and neuroprotective effects as well as the ability to reduce reactive oxygen species, protect the blood-brain barrier, modulate mitochondrial function, and regulate apoptosis. Considering these pharmaceutical characteristics, pinocembrin has potential as a drug to treat ischemic stroke and other clinical conditions. In this review, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 73 publications
2
86
0
2
Order By: Relevance
“…Pinocembrin acts at multiple targets (Lan et al, 2016) and has been shown to offer protection after cerebral ischemia (Shi et al, 2011; Wu et al, 2013). We demonstrated here that pinocembrin can significantly improve neurologic function, lessen brain injury volume, and decrease brain water content of ICH mice in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pinocembrin acts at multiple targets (Lan et al, 2016) and has been shown to offer protection after cerebral ischemia (Shi et al, 2011; Wu et al, 2013). We demonstrated here that pinocembrin can significantly improve neurologic function, lessen brain injury volume, and decrease brain water content of ICH mice in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Pinocembrin (purity > 99%), a kind gift from Dr. Guanhua Du (Institute of Materia Medica, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, China), was dissolved in 20% hydroxypropyl- β -cyclodextrin (HP- β -CD, Sigma-Aldrich) as described previously (Lan et al, 2016; Liu et al, 2014). Animals were randomly assigned (http://www.randomizer.org/) to receive pinocembrin (2.5, 5, 10 mg/kg) or vehicle via tail vein (i.v.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include apocynin [66,67,68], baicalein [69], caffeine [70,71,109], curcumin [72,73,74], niacin [64], nicotine [64], pinocembrin [75,76,110], resveratrol [77,78,79,80,81,111], polyphenols [112], and tanshinone IIA [82,83,84]. However, the number of studies investigating the effects of these agents on neurodegeneration and cognitive performance is limited.…”
Section: Antioxidants Cognitive Decline and Blood-brain Barriermentioning
confidence: 99%